(untitled) (International Educators Conference, 2025)
The article examines the methodology for developing combinatorial abilities in preschool children through visual activities, highlighting their role in fostering critical thinking, creativity, and problem-solving skills. Visual activities, such as pattern creation, drawing, and assembling objects, serve as effective tools for nurturing combinatorial thinking by engaging children in sensory-rich and exploratory experiences. The study emphasizes the importance of age-appropriate and progressively complex tasks, the role of educators and parents in facilitating these activities, and the potential of integrating technology and cultural elements. It also discusses the necessity of inclusivity and the use of observational and structured assessments to evaluate children’s developmental progress. The proposed methodology provides a holistic approach to enhancing cognitive and creative capabilities in young learners, laying a strong foundation for their future growth and adaptability.